KETAHANAN DUA JENIS BIBIT EUCALYPTUS TERHADAP BAKTERI RALSTONIA SOLANACEARUM - Kusumaningsih, Karti Rahayu; Hadi, Didik Surya; Gunawan, Freddy (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2015)
.............